(untitled) (Terr@ Plural, 2020)
An UOPG is a specific area detailed in the Oporto Master Plan (PDMP) that as a subset of the city needs specific planning in terms of urban coherence, urban integration or obligation to a specific use or subset of specifications. According to the PDMP, the objective of making the study area a UOPG is “the recuperation of the internal part of the block of the Companhia Aurifícia through the rehabilitation of the existing buildings with architectonic value and valuing of green areas, contributing to the overall revival of Downtown Oporto”. The flagship of the proposal is the restoration and reconstruction of the block, creating a large cultural and commercial center integrated to the green area inside and outside the block, thus connecting the surrounding streets and increasing the permeability of pedestrians.